Learning from Franz L. Neumann : law, theory, and the brute facts of political life - Kettler, David; Wheatland, Thomas (Anthem Press, 2019)
"Learning from Franz Neumann" examines the political and legal thought of Franz Neumann in relation to the contemporary decline of the social welfare state and the rise of populism.